2022-VA-1026-ESGO The case of laparoscopic retransplantaion of the ureter – Boari flap technique. (20th October 2022) - Milnerowicz-Nabzdyk, Ewa; Fiutowski, Marek; Nowak, Krzysztof; Borowiec, Zofia; Kalus, Marcin
Abstract : Introduction/Background: Presenting the method of laparoscopic retransplantation of the ureteron the case of deep infiltrating endometriosis (DIE) with the technique of Boariflap Methodology: 39 – year old lady with the history of multiple intervention due to DIE. The lastredical surgery with the huger rectovaginal nodule and ureteric dissection due tothe infiltration of parametrium and extended hysterectomy due to DIE. She hadprotective JJ stenting of the right ureter. 3 months later after removing of thestent she had stenosis of right ureter and repair surgery was needed. Results: The patient had proposed the laparoscopic procedure of repairing the ureter.She had CT scan of the pelvis and the location of the stenosis was localized.Due to lack of the lumen of the ureter on a UroCT on the 5 cm middle length ofthe ureter the Boari flap technique of the ureter retransplatation was proposed.And performed.JJ stent was removed from the ureter 6 weeks after surgery. Conclusion: The patient was completely free of complains and the proper lumen and functionof the ureter was confirmed on urography and in cystoscopy. Laparoscopy is aperfect method to repair the ureteric complication even with use of morecomplicated method.